If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6y + 3) + -16y = 52 Reorder the terms: 4(3 + 6y) + -16y = 52 (3 * 4 + 6y * 4) + -16y = 52 (12 + 24y) + -16y = 52 Combine like terms: 24y + -16y = 8y 12 + 8y = 52 Solving 12 + 8y = 52 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 8y = 52 + -12 Combine like terms: 12 + -12 = 0 0 + 8y = 52 + -12 8y = 52 + -12 Combine like terms: 52 + -12 = 40 8y = 40 Divide each side by '8'. y = 5 Simplifying y = 5
| X(.10)=1375 | | -3x+8y=-38 | | 12*x-(2*x+18)=2(5*x-9) | | 8+2n= | | 8(f-2)+4-2f=3f+36 | | 5y-4+y=59+2y-5y | | 7hn=5 | | 7(m-6)=4 | | -2y+4y=10 | | 15c^2+14c+3=0 | | whatdoesy= | | 6(3x-4)+54=3(x+11) | | 1.2x+7=13+x | | 14v=0 | | 5(x-2)-3*x=2(x-6) | | 81x^2+10=110 | | r+2.82=6.82 | | 9n=h | | 14+23=35+16 | | 5y+3x=349 | | f+2=20 | | 9(x+3)=4*x-3 | | 1.5(6x-0.3)= | | log(x)=0.80 | | pn=8 | | 80+10z=240 | | 9(x+3)=2+14*x | | m-11=2.4 | | sinx=0.41 | | -7(1-4*x)=13(2*x-3) | | 100+.80x=70+.90x | | 2x-6=4x+3 |